Pipelines 2010 : climbing new peaks to infrastructure reliability--renew, rehab, and reinvest : proceedings of the 2010 Pipeline Division Specialty Congress, August 28-September 1, 2010, Keystone Colorado - Ruchti, George; Roode, Tom (American Society of Civil Engineers, 2010)
Proceedings of the Pipelines 2010 Conference, held in Keystone, Colorado, August 28-September 1, 2010. Sponsored by the Pipeline Division of ASCE. This collection contains 152 papers that examine evolving infrastructure assessment and monitoring techniques to help pipeline professionals improve the reliability of buried pipeline assets. As U.S. pipeline infrastructure ages and displays the effects of decades of inattention and neglect, new and emerging technologies can provide innovative solutions to current and future problems. This collection can help the pipeline professional evaluate existing pipeline assets and set priorities for rehabilitation or replacement; design new pipelines using life-cycle costs and considerations; and obtain quality construction within the confines of project scope and budget. Topics include: construction, planning, design, construction, infrastructure assessment and monitoring, and new and emerging technologies.
Keywords: Pipelines -- Congresses.; elektronické knihy; electronic books